Program Handsanitizer dan Masker Kain Gratis bagi Masyarakat Kurang Mampu di Sekitar Kampus Universitas Andalas dalam Rangka Mencegah Penularan COVID-19 - Afdal Afdal; Marzuki Marzuki; Ardian Putra; Trengginas Eka Putra Sutantyo; Dwi Pujiastuti; Mutya Vonnisa; Fadilla Monica; Yoci Darwita Putri; Sucy Lestari Wirma; Novia Dwi Agusri; Eldiani Arifya; Muldarisnur Muldarisnur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
COVID-19 has become a terrifying thing for everyone. The government has made several decisions to prevent the spread of this disease, such as the program of physical distancing where economic, educational, entertainment, social, and even religious activities are requested to be carried out at home. The physical distancing policy also has a negative impact. This program results in reduced community mobility and a sluggish economy. Many people working in the informal sector with a daily income are experiencing difficulties. They struggle to meet their daily needs, especially buying face masks and hand sanitizers. This problem has inspired our community service team at the Department of Physics FMIPA Andalas University, West Sumatra (Indonesia), to make a program to overcome this problem by distributing 400 pieces of cloth masks and 120 bottles of hand sanitizer accessible to the public. This activity was very beneficial for the community, shown by their enthusiasm when the stock of cloth masks and hand sanitizers was gone in one hour. Most people do not use masks in outdoor activities, not because they do not want to wear them, but because of economic constraints. There is a need that is more important than a mask. To prevent the spread of COVID-19, especially to the poor, the government must provide them with free masks.